Improvement Effortsinterest in Visitingan Through Improving the Marketing Mix and Hospital Image in Indonesia - Umi Syarah; Duta Liana; Hasyim Hasyim (Lembaga Pengembangan Kinerja Dosen, 2024)
The level of repeat visit interest of patients in the Hospital Outpatient Clinic in April, June, July, August was relatively decreased. This decrease in repeat visit interest needs to be further examined to understand the factors involved. This study is to link the marketing mix implemented by the Hospital and the hospital image to the repeat visit interest to the hospital through patient experience. This study aims to analyze the effect of the marketing mix and hospital image on the repeat visit interest to the hospital with patient experience as an intervening variable in the Hospital Outpatient Clinic. This study uses a quantitative analysis method with a cross-sectional research design. The sample calculation uses purposive sampling of 105. The study used a questionnaire as a research instrument with Likert scale measurements showing that there is a positive and significant influence both simultaneously, directly, and indirectly between the marketing mix and hospital image on the repeat visit interest to the hospital with patient experience as an intervening variable in the Hospital Outpatient Clinic. Thus, the research hypothesis is accepted. Implications need to improve the hospital image through various media, improve the direction system, improve communication between doctors and patients and follow-up after visits